Features of the Modern Protectionism of the US and the EU towards Russia - A. A. Sidorov (Vestnik MGIMO-Universiteta)
The article examines the current trends and features of US and EU protectionism towards Russia, its possible consequences and ways of response. Protectionism has been increasing since 2020, which is manifested in the intensification of the use of existing instruments and the development of the new ones.The article analyzes possible consequences of the spike in countervailing investigations by the US against Russia. The author highlights possible application of similar restrictive measures by other partners as an additional risk. An unprecedented event is the US Department of Commerce review of Russia’s status as a market economy country for purposes of antidumping duty investigations. Non-market economy status expands the capabilities of the US to “overcount” dumping and impose duties, thus impeding the activity of Russian companies on foreign markets. The US acknowledged for now that there does not exist a sufficient degree of evidence to justify a change in Russia’s market economy designation, nevertheless, one cannot rule out such attempts in the future.In the EU context, the practice of energy adjustments, which results in overstated production costs, normal value and anti-dumping duties for Russian goods, is continued. A new protectionist step is the publication of the report “On significant distortions in the economy of the Russian Federation for the purposes of trade defence investigations”, which lays an additional basis for the continuation and strengthening of restrictive measures. The article analyzes a new instrument of environmental protectionism, the EU’s carbon border adjustment mechanism, a levy on imported products based on the embedded CO2 emissions. The measure will affect important positions of the Russian exports – cement, electricity, fertilizers, iron & steel and aluminum. The mechanism can be considered an attempt to make up for the EU’s lack of natural competitive advantages in mineral raw materials and to impose its vision of economic policy goals on the rest of the world.In conclusion, the author highlights features of American and European protectionism towards Russia – active employment of the role of the state in the economy factor as well as environmental factor as pretexts for introducing or tightening restrictive measures.The main ways of Russia’s response to new challenges can be the use of the WTO platform in cooperation with other countries, the search for new economic levers in relations with the partners (including application of trade defence measures), the detection of possible market distortions in the EU and the US for possible use in EAEU investigations.